Effects of an intervention to reduce fear of falling and increase physical activity during hip and pelvic fracture rehabilitation. (6th July 2020) - Pfeiffer, Klaus; Kampe, Karin; Klenk, Jochen; Rapp, Kilian; Kohler, Michaela; Albrecht, Diana; Büchele, Gisela; Hautzinger, Martin; Taraldsen, Kristin; Becker, Clemens
Abstract: Background: fear of falling and reduced fall-related self-efficacy are frequent consequences of falls and associated with poorer rehabilitation outcomes. To address these psychological consequences, geriatric inpatient rehabilitation was augmented with a cognitive behavioural intervention ("Step by Step") and evaluated in a RCT. Methods: one hundred fifteen hip and pelvic fracture patients (age = 82.5 years, 70% female) admitted to geriatric inpatient rehabilitation were randomly allocated to the intervention or control group. The intervention consisted of eight additional individual sessions during inpatient rehabilitation, one home visit and four telephone calls delivered over 2 months after discharge. Both groups received geriatric inpatient rehabilitation. Primary outcomes were fall-related self-efficacy (short falls efficacy scale-international) and physical activity as measured by daily walking duration (activPAL3™ sensor) after admission to rehabilitation, before discharge and 1-month post-intervention. Results: in covariance analyses, patients in the intervention group showed a significant improvement in fall-related self-efficacy ( P  = 0.025, d  = −0.42), but no difference in total daily walking duration ( P  = 0.688, d  = 0.07) 1-month post-intervention compared to the control condition. Further significant effects in favour of the intervention group were found in the secondary outcomes "perceived ability to manage falls" ( P  = 0.031, d  = 0.41), "physical performance" (short physical performance battery) ( P  = 0.002, d  = 0.58) and a lower "number of falls" ( P  = 0.029, d  = −0.45). Conclusions: the intervention improved psychological and physical performance measures but did not increase daily walking duration. For the inpatient part of the intervention further research on the required minimum intensity needed to be effective is of interest. Duration and components used to improve physical activity after discharge should be reconsidered.